An interval type-2 fuzzy QUALIFLEX approach to measure performance effectiveness of ballast water treatment (BWT) system on-board ship - Demirel, Hakan; Akyuz, Emre; Celik, Erkan; Alarcin, Fuat (TAYLOR & FRANCIS LTD, 2019)
Ballast water is of paramount importance for safe and efficient shipping operation since it provides ship's strength and stability. The ballast water, on the other hand, poses serious marine ecological problems due to the non-indigenous species (NIS) carried in sea water. The International Maritime Organisation introduced International Convention for the Control and Management of Ships' Ballast Water and Sediments (BWM Convention) to prevent the spread of harmful species from one region to another via ballast water. According to the convention, each ship must be equipped with a proper ballast water treatment system (BWTS). In this context, this paper is aimed at measuring the performance effectiveness of current BWTS used in ships. To achieve this purpose, a Qualitative Flexible (QUALIFLEX) method is used under interval type-2 fuzzy sets (IT2FSs) environment. While the QUALIFLEX handles all possible permutations of the alternatives for outranking, the IT2FSs deal with uncertainty this paper provides practical benefits to ship owners, ship's safety inspectors, managers and marine environmentalists during decision-making progress of the BWTS settlement on-board ship.
Keywords: Maritime environment; ballast water system; decision-making; IT2FS; QUALIFLEX; MARITIME TRANSPORTATION; RISK; SETS; MANAGEMENT; DEMATEL; AHP; STRATEGIES; TOPSIS; MODEL; MCDM; Engineering